EVALUASI METODE PEMBELAJARAN DIMASA PANDEMI MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Ayu Rohmawati; Fitroh Resmi (Jurnal Matematika dan Sains (JMS), 2021)
E-learning is a learning media that is being used 100% in various universities. Because it is still new, elearning needs to be evaluated to make it even better. The purpose of this study is to evaluate e-learning tofind out how much the method can be accepted by students. This study uses the AHP method because thissystem is able to analyze using a number of criteria in the selection of practical courses. The method is doneby comparing the matrix of a number of criteria from the results of student questionnaire forms. Theresults show that students still prefer face-to-face methods rather than e-learning because face-to-face materialis more easily absorbed and interactions with lecturers are more interwoven than using e-learning.Keywords : e-learning, analytical hierarchy process, face to face